Influencing Factors the Quality of Life in the Children with Cochlear Implants - Syed Bilal Hussain Shah; Muhammad Ali; Abdul Hakim; Kamran Zamurrad Malik; Kashif Obaid Niazi; Shakeel Ahmed (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the effect of cochlear implants on quality of life in the children.